Resveratrol as Add-on Therapy in Subjects With Well-Controlled Type 2 Diabetes: A Randomized Controlled Trial - Timmers, Silvie; de Ligt, Marlies; Phielix, Esther; van de Weijer, Tineke; Hansen, Jan; Moonen-Kornips, Esther; Schaart, Gert; Kunz, Iris; Hesselink, Matthijs K.C.; Schrauwen-Hinderling, Vera B.; Schrauwen, Patrick (Diabetes care, 2016)
To determine whether resveratrol supplementation can improve insulin sensitivity and promote overall metabolic health on top of standard diabetes care. Seventeen subjects with well-controlled type 2 diabetes (T2D) were treated with placebo and 150 mg/day resveratrol (resVida) in a randomized double-blind crossover study for 30 days. The main outcome measure was insulin sensitivity by the hyperinsulinemic-euglycemic clamp technique. Hepatic and peripheral insulin sensitivity were not affected by resveratrol treatment. Intrahepatic lipid content also remained unaffected by resveratrol; however, the change in intrahepatic lipid content correlated negatively with plasma resveratrol levels (R = -0.68, P = 0.03). Intramyocellular lipid content increased in type 2 muscle fibers (P = 0.03), and systolic blood pressure tended to decrease (P = 0.09) upon resveratrol treatment. In addition, resveratrol significantly improved ex vivo mitochondrial function (state 3 and state U respiration upon malate with octanoyl-carnitine, P < 0.005). Intriguingly, a correlation was found between plasma levels of a metabolite of resveratrol (dihydroresveratrol) and the metformin dose used by the patients (R = 0.66, P = 0.005), suggesting an interaction between metformin and resveratrol. It could be speculated that the lack of a resveratrol-induced insulin-sensitizing effect is caused by this interaction. Resveratrol supplementation does not improve hepatic or peripheral insulin sensitivity. Our results question the generalized value of resveratrol as an add-on therapy in the treatment of T2D and emphasize the need to perform studies in drug-naive patients with T2D or subjects with prediabetes.